2021
DOI: 10.3390/pharmaceutics13040447
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Nanocarriers for Ophthalmic Administration: Towards Experimental Design Implementation

Abstract: Nanotherapeutics based on biocompatible lipid matrices allow for enhanced solubility of poorly soluble compounds in the treatment of ophthalmic diseases, overcoming the anatomical and physiological barriers present in the eye, which, despite the ease of access, remains strongly protected. Micro-/nanoemulsions, solid lipid nanoparticles (SLN) or nanostructured lipid carriers (NLC) combine liquid and/or solid lipids with surfactants, improving drug stability and ocular bioavailability. Current research and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 152 publications
0
37
0
1
Order By: Relevance
“…The addition of HA produced a slight increase in average size and PI and a slight ZP reduction, maintaining a strongly positive potential that favours the stability of the system through repulsion by electrostatic forces between particles [ 56 ]. Optimized bLF-LIP were characterized morphologically by imaging using cryo-TEM ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of HA produced a slight increase in average size and PI and a slight ZP reduction, maintaining a strongly positive potential that favours the stability of the system through repulsion by electrostatic forces between particles [ 56 ]. Optimized bLF-LIP were characterized morphologically by imaging using cryo-TEM ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows predicting the instability courses of liposomes earlier than detected by other methods [ 28 ]. Furthermore, several authors have reported that liposomal particle size bellow 90 nm allows for better stability of the colloidal dispersion because gravitational phase partition is avoided by Brownian motion [ 56 ]. Moreover, the high value of ZP, over +20 mV, avoids electrostatic interaction between particles and the consequent phenomena of instability [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the work of Pinto et al observed both an increase and a decrease, depending on the ratio of solid to liquid lipid and they highlight the importance of the ratio of saturated to unsaturated fatty acids [ 39 ]. Such differing results between experimental reports demonstrate the importance of careful design when specific properties are required but that varying the lipids, the ratios and the surfactant will all have an effect that can best be determined by a carefully executed DOE [ 32 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, reaching the eye, especially the inner part, is a challenge both through topical and systemic administration. Topical administration is limited by eye physiological barriers, such as the cornea, which limit the access of xenobiotics [14], but also by some protection mechanisms, like blinking, tearing, and drainage, which promote a quick clearance of the drug [15]. On the other hand, it is equally difficult to make a drug reach the eye from the inside, due to the blood-aqueous barrier, which works similarly to the blood-brain barrier, preventing drug diffusion from blood to retina, through the intervention of uveal capillary endothelia and ciliary epithelia.…”
Section: Introductionmentioning
confidence: 99%